The Influence of Entrepreneurship Education and Business Mentoring on the Success of People-Centric Economic MSMEs in Nganjuk Regency - Farel Ilham Pamungkas; Sugeng Hadi Utomo; Farida Rahmawati; Agus Sumanto (STAI Miftahul Ula Nganjuk, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia's economy, but still face challenges in terms of human resource capacity and technology adoption. This research aims to analyze the influence of entrepreneurship education and business mentoring on the success of community-based micro, small, and medium enterprises (MSMEs) in Nganjuk Regency. Using a quantitative approach with the stratified random sampling technique, this research involves 196 MSMEs as respondents. Data were analyzed using multiple linear regression. The research results show that entrepreneurship education (?=0.338) and business mentoring (?=0.425) have a positive and significant impact on the success of MSMEs, both partially and simultaneously (R²=0.394). These findings imply the importance of integrating entrepreneurship education programs and business mentoring in efforts to develop community-based MSMEs.